Copper-Binding Small Molecule Induces Oxidative Stress and Cell-Cycle Arrest in Glioblastoma-Patient-Derived Cells. Issue 5 (17th May 2018) - Shimada, Kenichi; Reznik, Eduard; Stokes, Michael E.; Krishnamoorthy, Lakshmi; Bos, Pieter H.; Song, Yuyu; Quartararo, Christine E.; Pagano, Nen C.; Carpizo, Darren R.; deCarvalho, Ana C.; Lo, Donald C.; Stockwell, Brent R.
Summary: Transition metals are essential, but deregulation of their metabolism causes toxicity. Here, we report that the compound NSC319726 binds copper to induce oxidative stress and arrest glioblastoma-patient-derived cells at picomolar concentrations. Pharmacogenomic analysis suggested that NSC319726 and 65 other structural analogs exhibit lethality through metal binding. Although NSC319726 has been reported to function as a zinc ionophore, we report here that this compound binds to copper to arrest cell growth. We generated and validated pharmacogenomic predictions: copper toxicity was substantially inhibited by hypoxia, through an hypoxia-inducible-factor-1α-dependent pathway; copper-bound NSC319726 induced the generation of reactive oxygen species and depletion of deoxyribosyl purines, resulting in cell-cycle arrest. These results suggest that metal-induced DNA damage may be a consequence of exposure to some xenobiotics, therapeutic agents, as well as other causes of copper dysregulation, and reveal a potent mechanism for targeting glioblastomas. Graphical Abstract: Highlights: Picomolar NSC319726 arrests growth of glioblastoma-patient-derived cells NSC319726 binds to copper to induce oxidative stress using ambient oxygen NSC319726-derived ROS target purine deoxyribonucleosides to arrest cell cycle Abstract : Shimada et al. report that the compound NSC319726 arrests glioblastoma-patient-derived cells at picomolar concentrations. The compound binds to copper, generates ROS using ambient oxygen, and depletes nucleotide pools. This represents a new strategy for potently blocking the growth of glioblastoma.